Stray fields above artificial magnetic in-plane domains - Ahrend, Florian; Holzinger, D.; Fohler, Manuel; Pofahl, S.; Wolff, U.; DeKieviet, Maarten; Schaefer, R.; Ehresmann, A. (Journal of magnetism and magnetic materials, 2015)
The out-of-plane component of the magnetic stray field over a magnetically patterned exchange biased layer system was quantitatively determined by scanning µ-Hall measurements. These were performed over a Cu50nm/Ir17Mn8310nm/Co70Fe305nm/Au8nm layer system patterned by light-ion bombardment induced magnetic patterning. The system consists of artificial 5µm wide magnetic parallel-stripe domains with head-to-head/tail-to-tail magnetizations in adjacent domains. The experimental data were taken within a height range relevant for magnetic micro-particle transport (0.75-2.65µm). We fit the experimental results by two different simulation approaches and discuss the feasibility of extrapolating the simulations to even closer surface distances. The models are used to extract stray field data as they would be measured by an ideal point-like probe.
Gesehen am 23.09.2020